Study on Community Structure of Commercial Sea Cucumber in Intertidal Zone, Southeast Moluccas, and Tual, Moluccas - Jasmadi Jasmadi; Ismiliana Wirawati; Indyaswan Tegar Suryaningtyas; Sandi Permadi (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightEight species of sea cucumber was found in four intertidal location in Southeast Moluccas and Tual watersHolothuria atra had the highest densitySea cucumber biodiversity in Southeast Moluccas and Tual waters categorized as lowLocal culture can be used for sustainability of sea cucumber resources management AbstractA study on the community structure of sea cucumber in Southeast Moluccas and Tual needs to be done due to the important role of sea cucumber in both ecologically and economically sustainability. This study aimed to investigate the community structure of sea cucumber in this region as one of the supporting information for the utilization and management of the resources. A survey was conducted by sweeping the target area, by walking and also snorkeling. The location where each sea cucumber found was marked using a GPS, the specimen was weighed, and some were preserved for species analysis. Water quality was measured at each location, while the substrate and vegetation were recorded. This study revealed different composition of species in the investigated area. As many as 8 species of sea cucumber were found, in which four were of genus Holothuria, three were of genus Stichopus and the rest were of genus Bohadschia. Species H. atra has the highest density. In general, the diversity index was relatively low (< 2), the evenness index was 0-81 indicating that the community was depressed. Certain species dominated at most of the investigated sites (0.50-1), and a low margalef index is 0-1.7. To conclude, the community structure of sea cucumber in Tual and Southeast Moluccas was in a depressed condition.